Sądownictwo administracyjne na ziemiach polskich pod zaborami - Wiązek, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The paper is devoted to the issues related to the history of administrative justice in the Polish lands. It is an attempt to synthesise the beginning of the development of such jurisdiction, in complex political reality, and a constitutionally legal period in which the Polish nation was deprived of its sovereign statehood. Using mainly the method of legal comparison, which promotes the use of research subjects taken, the author seeks to present the problem in a possibly condensed way, finally forming a complete view on administrative justice in the Polish lands under occupation, while presenting it in a way that ensures proper perception by a potential reader.
Keywords: historia prawa; historia prawa administracyjnego; historia postępowań administracyjnych; sądy administracyjne; sądownictwo administracyjne; postępowanie administracyjne; ustrój sądów; sądownictwo